Uso de geotecnologias no estudo da organização socioespacial da Região Metropolitana de Aracaju - Santos, Antônio Santiago Pinto (2019)
Complex analytical elements are part of Aracaju Metropolitan Region - AMR, officially created by the Complementary Law number 25/1995, which congregates urban nuclei with diversified functions, especially with the urban expansion verified in the last decades of the twentieth century and the beginning of the present century. In this sense, urban and regional development implies the need for better planning and management of their spaces, considering the basic sanitation infrastructure, electricity, garbage collection, road system layout, transportation services besides public education, health and safety service provision. To this end, current legislation establishes general guidelines for the planning and management of “Common Public Interest Functions - CPIFs” in metropolitan regions. The area of this research covers the coastal municipalities of Aracaju, Barra dos Coqueiros, Nossa Senhora do Socorro and São Cristóvão where the estuarine complexes of the Sergipe and Vaza Barris rivers are located. Embedded in this scenario, there is an urban site with structuring axes that connect the municipalities in the process of conurbation. In this respect, the present research prioritized the general objective of analyzing the socio-spatial organization of the Aracaju Metropolitan Region through the use of geotechnologies as support tools for urban and regional planning. With the use of this technological resource, a digital spatial data base (BDDE) was formed and the landscape dynamics were mapped from 1984 to 2018, using socio-spatial variables from IBGE census sectors of the year 2010. Geographic space functions were identified through photointerpretation that enabled the mapping of land use in eleven thematic classes, adopted for their importance in this urban environment. The quantification of each class was made, highlighting the “Urban” class with 139.3 Km2 and “Mangrove” with 61.4 Km2 in the 2018 mapping. Cross-checks of the census data with the held classification, allowed the elaboration of a Basic Social Development Index, demonstrating, finally, that Geoprocessing technologies are efficient tools for spatial analysis and can be used as decision support for Urban and Regional Planning.